Content-Based Instruction and Student Competency Development in Indonesia’s Kurikulum Merdeka: A Literature Review - Shofiatuz Zakiyah; Aulia Rahmatika Nur Azizah (Universitas Islam Cordoba Banyuwangi, 2025)
This study examines the potential of Content-Based Instruction (CBI) in supporting student competency development within the framework of Indonesia’s Kurikulum Merdeka. Using a qualitative literature review approach, 15 peer-reviewed studies published between 2020 and 2024 were systematically selected and analyzed through thematic analysis. The findings indicate that CBI contributes to four main areas: improvement of academic language proficiency, enhancement of higher-order thinking skills, promotion of student autonomy, and increased learning motivation. However, challenges related to teacher preparedness and limited instructional resources remain significant barriers to effective implementation. This study contributes to the existing literature by clarifying the alignment between CBI principles and the competency-based orientation of Kurikulum Merdeka and by highlighting key considerations for curriculum design and teacher professional development in the Indonesian context. These findings offer implications for curriculum designers and teacher training programs under Kurikulum Merdeka.